2012
DOI: 10.1111/j.1742-1241.2011.02872.x
|View full text |Cite
|
Sign up to set email alerts
|

Fifteen years of continuous improvement of quality care of type 2 diabetes mellitus in primary care in Catalonia, Spain

Abstract: AimsTo assess the evolution of type 2 diabetes mellitus (T2DM) quality indicators in primary care centers (PCC) as part of the Group for the Study of Diabetes in Primary Care (GEDAPS) Continuous Quality Improvement (GCQI) programme in Catalonia.MethodsSequential cross-sectional studies were performed during 1993–2007. Process and outcome indicators in random samples of patients from each centre were collected. The results of each evaluation were returned to each centre to encourage the implementation of correc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
36
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(45 citation statements)
references
References 27 publications
6
36
0
3
Order By: Relevance
“…GEDAPS is described in detail elsewhere [5,6]. Briefly, GEDAPS was implemented in Catalonia, where there is a public health system, 70% of the population live in urban areas, and the prevalence of diabetes was approximately 4.7% when the programme began [5].…”
Section: Gedaps Programmementioning
confidence: 99%
See 2 more Smart Citations
“…GEDAPS is described in detail elsewhere [5,6]. Briefly, GEDAPS was implemented in Catalonia, where there is a public health system, 70% of the population live in urban areas, and the prevalence of diabetes was approximately 4.7% when the programme began [5].…”
Section: Gedaps Programmementioning
confidence: 99%
“…Generally, such programmes have been shown to impact positively on patients' care and health [2][3][4], including the GEDAPS programme (Group of Study of Diabetes in Primary Care) which was implemented in primary care in Catalonia, Spain between 1993 and 2002 [5,6]. GEDAPS resulted in improvements in process, intermediate and final outcomes when the patient population was considered as a whole [5,6]. It is however unclear whether quality improvement programmes, including GEDAPS, impact positively on all populations or whether a different approach is required for some hard to reach groups.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Attributes of health professionals regarding providing information about diabetes are among the factors that may be effective in reducing DFU (6). The aim of DFU prevention should be to teach self-foot care to patients and to examine their foot at each reconsultation.…”
Section: Introductionmentioning
confidence: 99%
“…In Spain, for example, primary care centres, which are similar to those participating in the present study, demonstrated significant improvements between 1993 and 2007 in process measures (such as measurement of HbA1c and lipid levels), intermediate outcome measures [including the proportion of patients with HbA1c ≤7.0% (53 mmol/mol), total cholesterol ≤ 200 mg/dl and blood pressure ≤ 140/90 mmHg], and microvascular complications 27, 28. Primary care–led structured care, with relatively limited but well‐focussed investment, can achieve quality of care for patients with diabetes, comparable to international best practice 7.…”
Section: Discussionmentioning
confidence: 72%